Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð¸Ð½Ñ‚Ñ€Ð°Ð¿Ð¾Ñ€Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð²Ð²ÐµÐ´ÐµÐ½Ð¸Ñ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÑÐ¿Ð»ÐµÐ½Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð½Ð° Ð²Ñ‹Ð¶Ð¸Ð²Ð°ÐµÐ¼Ð¾ÑÑ‚ÑŒ Ð°Ð»Ð»Ð¾Ñ‚Ñ€Ð°Ð½ÑÐ¿Ð»Ð°Ð½Ñ‚Ð°Ñ‚Ð° Ñ‚ÐºÐ°Ð½Ð¸ Ñ‰Ð¸Ñ‚Ð¾Ð²Ð¸Ð´Ð½Ð¾Ð¹ Ð¶ÐµÐ»ÐµÐ·Ñ‹ - Bozhok, G. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
The influence of intraportal introduction of cryopreserved splenocytes on the survival of thyroid tissue allograft was investigated. An acute allograft rejection after transplantation of thyroid tissue fragments in the absence of immunosuppressant for 35 days was established, whereas introduction of native splenocytes of donor’s origin into portal vein of the recipient’s liver 7 days prior to allotransplantation prolongs an allograft survival. This effect is not observed when using post-thaw splenocyte suspensions, probably due to the elimination of macrophages under the influence of cryopreservation factors.